Survey data on public perceptions of salmon aquaculture industry in Norway, Tasmania, and Iceland - Marit Schei Olsen; Eirik Mikkelsen; Karen A. Alexander; Ragnheidur Thorarinsdottir; Tonje C. Osmundsen (Data in Brief, 2024)
This article presents data collected using online surveys conducted in Norway, Tasmania (Australia) and Iceland, with the aim of exploring public perceptions of the salmon aquaculture industry in each country. A total of 2085 survey participants provided responses, with 1183 from Norway, 406 from Tasmania, and 496 from Iceland.The survey encompassed various aspects of attitudes towards and perceptions of the aquaculture industry. Participants were asked questions regarding their environmental concerns, trust in governance and management, and knowledge of the aquaculture industry in their respective country. Additionally, attitudes towards the industry were explored using questions related to preferences regarding information sources, perceptions of industry contributions, distribution of economic benefits, financial significance in local community, sustainability, and acceptance and tolerance of industry production. Respondents were also given the opportunity to provided text comments regarding the areas in which they thought the industry should become more sustainable. Demographic data on the respondents were collected, directly from the participants and from existing panel data from the survey company. However, the dataset excludes information on residence on the local level (postal code) to ensure anonymity of the respondents.The survey design was created by the SoLic-project (2019-2022, supported by the Research Council of Norway, no. 295114), drawing on the social license literature and the team's extensive research experience on topics related to the aquaculture industry, social acceptance, and legitimacy.The dataset presented in the article combines raw survey data with additional analysis data derived from grouping answer options or recoding data variables. The data provided in this article offers a valuable resource for researchers, industry representatives, public authorities, and other parties interested in salmon aquaculture. It enables comparative analyses and further investigations into public perceptions in Norway, Tasmania, and Iceland. This dataset can be used to explore a wide range of topics and extend the research conducted by the SoLic project team.